(untitled) (Fiep Bulletin - online, 2011)
Vibration is an oscillatory mechanical stimulus characterized by its frequency and amplitude. A possible clinical application of this stimulus, in appropriated conditions, it is the exercise in vibration platforms (whole body vibration). In consequence, the scientific interest in WBV exercises can aid to increase the knowledge on appropriate, safe and effective exercise protocols. PubMed is a service of the U.S. National Library of Medicine and the aim of this work is to identify, the scientific interest in WBV, evaluating the number of publications cited per year in the PUBMED in WBV alone and in the association with some clinical application. The searches were performed (October 2009) in the PubMed (http://www.ncbi.nlm.nih.gov/entrez/query.fcgi). It was shown that in the last six years the scientific interest in WBV exercise has strongly increased. It is shown a high NPB with elderly and low-back pain. The current evidence indicates that platforms can generate vibrations and the WBV exercises may be an effective intervention for musculoskeletal disorders in trained and untrained, as well as in older. Moreover, the scientific community would be interest in knowing more about this kind of exercises, as it can be seen with the increase of publications in the last years. In consequence, it is necessary to take care with the people that are undertaken WBV exercises because to their individual reactions and due to the limited scientific information in the literature. The presence of a professional when a person is undertaken a WBV in vibration platform is desirable.